2023
DOI: 10.3988/jcn.2023.19.1.83
|View full text |Cite
|
Sign up to set email alerts
|

National Estimates of Narcolepsy in Korea

Abstract: Background and Purpose Epidemiological data on narcolepsy are rare in South Korea. We aimed to provide an overview of the burden of narcolepsy and its temporal trend in South Korea. Methods Patients with narcolepsy were identified by their registration in the Rare and Intractable Disease (RID) register and the Health Insurance Review and Assessment database. Individuals registered in the RID program with the code V234 were considered as having ‘definite narcolepsy’, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Although narcolepsy can be noted with the same symptoms in both men and women, some studies have reported different prevalences depending on gender. For example, the prevalence is equally common in males and females [11], it is more common among men [19,20], or there is a greater prevalence in females than men [26,28].…”
Section: Information About Narcolepsy In Different Populationsmentioning
confidence: 99%
“…Although narcolepsy can be noted with the same symptoms in both men and women, some studies have reported different prevalences depending on gender. For example, the prevalence is equally common in males and females [11], it is more common among men [19,20], or there is a greater prevalence in females than men [26,28].…”
Section: Information About Narcolepsy In Different Populationsmentioning
confidence: 99%